Finite Element Analysis of Rail-End Bolt Hole and Fillet Stress on Bolted Rail Joints. Issue 1 (January 2017) - Zhu, Kaijun; Qian, Yu; Edwards, J. Riley; Andrawes, Bassem O.
A rail joint typically is one of the weakest elements of a track superstructure, primarily because of discontinuities in its geometric and mechanical properties and the high-impact loads induced by these discontinuities. The development of continuously welded rail has significantly reduced the number of rail joints, but many bolted joints remain installed in rail transit systems. Because of the unique loading environment of a rail transit system (especially high-frequency, high-repetition loads), defects related to bolted rail joints (e.g., joint bar failures, bolt hole cracks, and cracks in the upper fillet) continue to cause service failures and can pose derailment risks. Recent research in the Rail Transportation and Engineering Center at the University of Illinois at Urbana–Champaign has focused on investigating crack initiation in the bolt hole and fillet areas of bolted rail joints. Stress distribution was investigated at the rail-end bolt hole and upper fillet areas of standard, longer, and thicker joint bars under static loading conditions. Numerical simulations were organized into a comprehensive parametric analysis performed with finite element modeling. Preliminary results indicated that the longer joint bar performed similarly to the standard joint bar but the thicker joint bar reduced rail vertical displacement and rail upper fillet stresses compared with the standard joint bar. However, the thicker joint bar also may generate higher stresses at the rail-end bolt hole. Additionally, joint bar performance was dependent on the rail profile and bolt hole location.